الصراع النفسي والاجتماعي وعلاقتهما بالاكتئاب لدى عينة من طلبة جامعة دمشق في ضوء متغيري النوع والتخصص الدراسي (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يهدف البحث إلى معرفة العلاقة بين الصراع النفسي والاجتماعي وبين الاكتئاب لدى طلبة جامعة دمشق، وما إذا كانت توجد فروق دالة ًفي متوسطات درجات الصراع النفسي والاجتماعي والاكتئاب بين الذكور والإناث، وكذلك بين طلبة التخصصات العلمية و طلبة التخصصات الأدبية. تكونت عينة البحث من(350) طالباً وطالبة ، منهم (165) طالبا و(185) طالبة. استخدم الباحث مقياس الصراع النفسي والاجتماعي، وقائمة بيك وآخرين للاكتئاب. وقد استخرج للمقياسين معاملات الصدق والثبات اللازمة. وأهم النتائج التي أسفر عنها البحث، وجود علاقة إيجابية دالة بين كل من الصراع النفسي والاجتماعي وبين الاكتئاب. بالإضافة إلى ذلك وجدت  فروق دالة جوهرياً بين متوسط درجات الذكور ومتوسط درجات الإناث في الصراع النفسي والاجتماعي والاكتئاب لصالح الإناث. ولم تظهر النتائج وجود فروق دالة في متوسط درجات الصراع النفسي والاجتماعي والاكتئاب بين طلبة التخصصات العلمية وطلبة التخصصات الأدبية. This research aimed to know the relationship between psychological social conflict and depression among Damascus University students whether existing any significant differences between the means of psychological social conflict and depression degrees with respect to male and female, Science and Literate Students. The sample of the research consisted of (350) students both sexes, (165) male and (185) female students. The researcher used psychological social conflict and (BDI-II) scales. Validity and reliability of both tools were concluded. The results revealed that, there was a significant positive correlation between Psychological and social conflict and depression. The results also revealed that significant differences were observed between the means of psychological social conflict and depression between male and female students for the female. Also it showed that is no significant differences between the means of psychological social conflict and depression among Science and Literate Students.